Experimental study on acoustic condensation fog elimination in traveling wave tube. Issue 2 (March 2021) - Liu, Chang; Tian, Zhangfu; Zhao, Yun; Zhou, Hefeng
Abstract: Acoustic condensation artificial fog elimination has the advantages of wide application range, good economy, flexible and controllable operation area, and does not affect traffic operation. The characteristics of the fog, the frequency and intensity of the acting sound waves have an important influence on the effect of condensation and fog elimination. This paper studies the influence of the frequency of fog on the microscopic particle size distribution and the change of light transmission in the process of fog elimination from both theoretical and experimental aspects. The research results show that for natural fog conditions with low concentration, the time of pure sound wave action takes several minutes to tens of minutes. Under the condition of high-concentration artificial fog, the anti-fog time can be shortened to tens of seconds. Simulations and experiments have both confirmed that sound waves can significantly promote fog elimination, and there is an optimal frequency between 200Hz-700Hz.